2019
DOI: 10.1002/hyp.13606
|View full text |Cite
|
Sign up to set email alerts
|

Calibration method affects the measured δ2H and δ18O in soil water by direct H2Oliquid–H2Ovapour equilibration with laser spectroscopy

Abstract: The direct H 2 O liquid -H 2 O vapour equilibration method utilizing laser spectroscopy (DVE-LS) is a way to measure soil pore water stable isotopes. Various equilibration times and calibration methods have been used in DVE-LS. Yet little is known about their effects on the accuracy of the obtained isotope values. The objective of this study was to evaluate how equilibration time and calibration methods affect the accuracy of DVE-LS. We did both spiking and field soil experiments. For the spiking experiment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The effective failure rate is at or below 5% when soil samples are double bagged (Wassenaar et al, 2008), which also avoids interlaboratory isotope contamination (Mueller et al, 2014;Orlowski, Pratt, & McDonnell, 2016) and allows the soil samples to be processed with less potential to evaporate compared with isotope-ratio mass spectrometry methods (Wassenaar et al, 2008). Work by Orlowski et al (2016) found that conventional methods, such as cryogenic distillation, may be prone to large offsets between measurements and reference waters, and assessments of the errors within our data show our approach is consistent with a recent methodological assessment study (Wang, Si, Pratt, Li, & Ma, 2020), which reported measurement errors on spiked samples of known isotopic composition. Sample handling and analysis was maintained consistent across all treatments and locations; thus, differences between samples are expected to be caused by field conditions and not normal laboratory procedures.…”
Section: Laboratory Analysis and Post-processingsupporting
confidence: 86%
“…The effective failure rate is at or below 5% when soil samples are double bagged (Wassenaar et al, 2008), which also avoids interlaboratory isotope contamination (Mueller et al, 2014;Orlowski, Pratt, & McDonnell, 2016) and allows the soil samples to be processed with less potential to evaporate compared with isotope-ratio mass spectrometry methods (Wassenaar et al, 2008). Work by Orlowski et al (2016) found that conventional methods, such as cryogenic distillation, may be prone to large offsets between measurements and reference waters, and assessments of the errors within our data show our approach is consistent with a recent methodological assessment study (Wang, Si, Pratt, Li, & Ma, 2020), which reported measurement errors on spiked samples of known isotopic composition. Sample handling and analysis was maintained consistent across all treatments and locations; thus, differences between samples are expected to be caused by field conditions and not normal laboratory procedures.…”
Section: Laboratory Analysis and Post-processingsupporting
confidence: 86%
“…c) Instrumental precision, repeatability, memory effects of isotope ratio mass spectrometry and laser spectroscopy measurements of water samples, possible off-set and deviations between mass spectrometry and laser spectroscopy measurements (Penna et al, 2010(Penna et al, , 2012Wassenaar et al, 2014;Wang et al, 2020), as well as contamination issues with organic compounds in laser spectroscopy Martín-Gómez et al, 2015).…”
Section: Heterogeneity and Uncertainty In Isotope-based Estimates Of mentioning
confidence: 99%
“…The direct vapor equilibration laser spectrometry (DVE-LS) method first published by Wassenaar et al (2008) has facilitated a way for fairly convenient, high-throughput stable isotope analysis of water bound to the soil matrix, rocks, or plant tissue. Instead of physically extracting water, the method employs analysis of a corresponding vapor phase and thereby bypasses many of the previously necessary, laborious sample preparation steps.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the DVE-LS method has considerably simplified matrix-bound water stable isotope analysis. However, it is not yet perfect, and several studies have aimed at specifically testing and/or improving accuracy, precision, and/or the general applicability of the protocol originally described by Wassenaar et al (2008), e.g., by comparison with other methods of matrix-bound water stable isotope analysis. Hendry et al (2015) compared DVE-LS results against isotope analyses of water obtained from piezometers and mechanical squeezing of geologic core samples.…”
Section: Introductionmentioning
confidence: 99%